Effect of oral administration of robenacoxib on experimentally-induced anterior uveitis in normal cats - Sharpe, Emily (Kansas State University, 2018)
Objectives- To determine the effect of oral robenacoxib on experimentally-induced anterior uveitis, and to evaluate the ability of robenacoxib to cross an intact blood-aqueous barrier. Animals- Twelve healthy adult domestic shorthair cats. Procedures- Cats in the treatment group (n=6) received oral robenacoxib (1.51 ± 0.36 mg/kg ) once daily beginning 1 day before experimental induction of uveitis by anterior chamber paracentesis (ACP) and continuing 1 day after paracentesis. Anterior chamber paracentesis was performed using a 30 g needle attached to a 1 mL syringe, and 100 µL of aqueous humor were aspirated over 3-5 seconds. Anterior chamber fluorophotometry was performed in both eyes of each cat immediately before ACP (time 0), and at 6, 24, and 48 hours after ACP. An independent t-test was used to compare percent fluorescein increase in treatment versus control cats at each time point. Values of p<0.05 were considered significant. Concentrations of robenacoxib in aqueous humor were measured using liquid chromatography and mass spectrometry. Results- There was no statistically significant difference between the ACP and control eye at time 0 (p=0.322). When comparing the percent fluorescein increase between treatment and control groups, there was no statistically significant difference at any time point (p>0.05). Robenacoxib was present in small but detectable levels in 5/6 cats in the treatment group. Conclusions and clinical relevance- Administration of oral robenacoxib did not significantly lessen experimentally-induced anterior uveitis in normal cats, as assessed by fluorophotometry. Low concentrations of aqueous humor robenacoxib were detectable in the majority of cats receiving the drug.
Effect of oral administration of robenacoxib on inhibition of paracentesis-induced blood-aqueous barrier breakdown in normal cats
Keywords: Robenacoxib; Blood-aqueous barrier; Feline; Fluorophotometry